Boosting Customer Growth: The Impact of Service Excellence and Product Quality at Bank Muamalat KCP Gowa, South Sulawesi - Wati, Mirna; Mustamin, Asyraf; Supriadi, Supriadi; Nur, Awal (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2024)
Service excellence and product quality are two factors that can affect customer satisfaction. Customer satisfaction will drive customers' growth. For example, customers who are satisfied with the services or products offered will promote Islamic banking products/services to others, which will affect the growth in the number of customers. The purpose of this study was to determine the effect of service excellence and product quality on customer growth at Bank Muamalat KCP Gowa. The number of samples in this study were 100 respondents, using a quantitative approach. The data collection technique used a questionnaire, and the sample calculation technique used the slovin formula. The results of this study indicate that the sig. value of 0.000 < 0.05 and the t-count value of 5.146> t-table 1.983 for the service excellent variable and the value of 0.008 t-table 1.983 for the product quality variable. Furthermore, the value of 0.000 < 0.05 and F count of 40.856 > F table of 3.090 were obtained. The implication of this research shows the excellent service quality enhances customer growth, as well as the high product quality improves customer growth. The excellent service and product quality provided will create satisfaction for customers to recommend to others and support the growth of the number of customers at Bank Muamalat KCP Gowa.